New insight of square stepping exercise in immune fine-tuning for anticipating emerging pandemics - Cha, Hyo-Jeong; Hong, Changwan (Animal cells and systems, 2024)
The COVID-19 pandemic has significantly impacted human life, posing serious physical and psychological threats, particularly to the elderly. While individuals of all ages are susceptible to contracting COVID-19, older people face a heightened risk of developing various diseases due to age-related immunophysiological changes and preexisting health conditions. The interplay between immune health and physical activity is believed to hold even greater significance during a pandemic. Recent findings from our research indicate that the intervention of square stepping exercise (SSE), characterized by a rhythmic and controlled stepping pattern, resulted in increased levels of Brain-Derived Neurotrophic Factor (BDNF) in the elderly. BDNF, known to influence not only nerve cells but also immune cells, suggests a potential link between SSE and immune system modulation. Consequently, this exercise regimen holds promise in counteracting age-related immunophysiological changes, fine-tuning immune responses, and mitigating the severity of potential new virus outcomes, such as 'Disease X.' This review aims to underscore the significance of integrating SSE as a home-based program, serving as a potent tool to enhance immune resilience, prepare for future potential pandemics, and empower older individuals during challenging times. Through the practice of SSE, older adults may strengthen their ability to navigate the challenges posed by pandemics and maintain a sense of control over their well-being.